FiPaWeb: method to reduce the complexity of web search - Romagnano, María R. (2014)
In this work the FiPaWeb method is proposed to group the pages; and at the same time keep the overlap between them; without losing information. The method has five stages. In the first stage the web search is performed. In the second stage the relevant pages are selected. In the third stage the value of each service is determined for each page. In the fourth stage the pages are grouped based on established criteria. Finally, in the fifth stage, the system accesses the groups that contain only the information requested by the user in a query. (Párrafo extraído del texto a modo de resumen)